On-call work in the Netherlands: trends, impact, and policy solutions - Burri, Susanne D.; Heeger-Hertter, Susanne; Rossetti, Silvia (Geneva, 2018)
"Flexible work has steadily increased in the Dutch labour market and on-call employment represents the fastest growing group. Although on-call work is both the largest and the least institutionally regulated form of flexible employment, little is known on its developments and impacts. The main objective of this study, commissioned by the ILO, is to compensate this gap and provide an insight of the most relevant legal and socio-economic issues concerning the forms of on-call work that are used in the Netherlands. The paper relies both on available data and own research.é